Fifth nocturne - Leybach, J. (Joseph), 1817-1891 (McKinley Music Co. (Chicago, Ill.), 1907)
Piano; Violin; Finding aid: http://library.truman.edu/manuscripts/D4-DavisMusic.asp; Violin and piano score for "Fifth Nocturne".